2019
DOI: 10.1021/jacs.9b06194
|View full text |Cite
|
Sign up to set email alerts
|

Cleaving Carboxyls: Understanding Thermally Triggered Hierarchical Pores in the Metal–Organic Framework MIL-121

Abstract: Carboxylic acid linker ligands are known to form strong metal−carboxylate bonds to afford many different variations of permanently microporous metal−organic frameworks (MOFs). A controlled approach to decarboxylation of the ligands in carboxylate-based MOFs could result in structural modifications, offering scope to improve existing properties or to unlock entirely new properties. In this work, we demonstrate that the microporous MOF MIL-121 is transformed to a hierarchically porous MOF via thermally triggered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 55 publications
1
49
0
Order By: Relevance
“…2 H NMR offers a straightforward method for the investigation of methane adsorption locations and dynamics within MOFs pores. [ 78 ] Methane adsorption behavior on several representative MOFs has been examined by VT 2 H NMR spectroscopy. [ 77 ] Figure 7c displayed the static VT 2 H static NMR spectra of singly deuterated methane (CH 3 D) adsorbed on α‐Mg 3 (HCO 2 ) 6 .…”
Section: Ssnmr Characterization Of Mofsmentioning
confidence: 99%
“…2 H NMR offers a straightforward method for the investigation of methane adsorption locations and dynamics within MOFs pores. [ 78 ] Methane adsorption behavior on several representative MOFs has been examined by VT 2 H NMR spectroscopy. [ 77 ] Figure 7c displayed the static VT 2 H static NMR spectra of singly deuterated methane (CH 3 D) adsorbed on α‐Mg 3 (HCO 2 ) 6 .…”
Section: Ssnmr Characterization Of Mofsmentioning
confidence: 99%
“…Next to high porosity, defined structures and chemical versatility, these materials may feature stimuli‐responsive structure, which, in turn, allows for reversible/irreversible structural transformation such as crystal‐to‐amorphous or crystal‐to‐crystal ones . The reversible transformations induced by external stimuli such as mechanical constrains, guest uptake, temperature, UV‐VIS light exposure and others are utilized for controllable gas adsorption, separation and catalysis . The defined structural flexibility expands the utility of MOFs as “smart” materials for remotely controlled sensors or communication devices such as memory devices and optical switchers.…”
Section: Figurementioning
confidence: 72%
“…Chen et al . [ 33 ] suggested that the thermal trigger decarboxylation method obtained hierarchical porous MOF to improve the adsorption capacity of MIL-121 to CO 2 , C 2 H 2 , C 2 H 4 and CH 4 gases. In this paper, the control of MIL-121 morphology and size was investigated by adjusting the hydrothermal reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature [32], the surface area of MIL-121 is only 162 m 2 g −1 , which is extremely detrimental to its application to gas adsorption separation. Chen et al [33] suggested that the thermal trigger decarboxylation method obtained hierarchical porous MOF to improve the adsorption capacity of MIL-121 to CO 2 , C 2 H 2 , C 2 H 4 and CH 4 gases. In this paper, the control of MIL-121 morphology and size was investigated by adjusting the hydrothermal reaction conditions.…”
Section: Introductionmentioning
confidence: 99%